Prioritas Pengembangan Pariwisata Di Kawasan Minapolitan Kedonganan, Kecamatan Kuta, Kabupaten Badung - Natasya, Natasya; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
Kedonganan Beach is a tourist destination located in Kedonganan, Kuta, Badung, Bali. It was one crowded beach as a place to visit to when you want to enjoy a dinner in the Southern of Bali. As a Minapolitan Area, the area is indeed in need of a strategic plan to help it to develop. It was famous for their seafood and beautiful view from the ocean. Development of a tourist destination depends on their planning on managing the potency. This study wants to analyze the priority of their Spatial Plans. The plans will determine how the space will be developed for a tourist with minapolitan based destination. The study uses the SWOT analysis to describe the Strengths, Weaknesses, Opportunities, and Threats from the Spatial Plans. The study determines that the priority of the Spatial Plans is developing structural and accessibility for the tourist and locals. Kedonganan also needs varied tourist attractions to attract different kind of tourists to visit. It is also important to have a sustainable development plan. Base on this study, the researcher concludes there should be some strategic plans to develop Kedonganan. One, is for government build the area to become a better tourist destination by improving the facilities of the destination. By using the social capital the locals have, locals can improve their human resources as one of the most important factors in developing tourism. Lastly, stakeholders should develop tourism based on the traditional culture that the village has had rather than adding more varied tourist attractions that does not showcase the cultural characteristic. Keywords: minapolitan, tourist destination, tourism, development